Prospek Ekonomi Syariah di Indonesia pada Tahun 2024-2028 - Farid Ma’ruf; Imam Fachruddin (Prodi Ekonomi Syariah, Fakultas Syariah, Institut PTIQ Jakarta, 2023)
This research is an in-depth literature review on the prospects of Shariah economy in Indonesia from 2024 to 2028. Considering the urgency of global Shariah economic growth and Indonesia's commitment to it, this study provides profound insights into the fundamental concepts of Shariah economics, its principles, and its evolution in Indonesia. The research problem formulation reflects a response to the journey of Shariah economics, identifying its challenges and opportunities. The research aims to contribute to the understanding of Shariah economics by exploring its principles, its development in Indonesia, and the impact of global trends. The research methodology includes the approach, data sources, data collection techniques, and data analysis methods. In exploring the prospects of Shariah economy from 2024 to 2028 in Indonesia, this study highlights global trends, the Shariah Economic Masterplan of Indonesia 2019-2024, and the role of the government. The research findings reveal a deep understanding of the challenges and opportunities of Shariah economics, emphasizing government support and key sectors. The conclusion of this research summarizes the prospects of Shariah economics in Indonesia, emphasizing the need for strategic planning and cross-sector collaboration to optimize the potential of Shariah economics. The implications of this research are relevant to policymakers, practitioners, and academics involved in shaping the future of Shariah economics in Indonesia. By providing a strong foundation of understanding, this research encourages collaboration to advance Shariah economics towards a sustainable and inclusive future.